2019
DOI: 10.1016/j.ypmed.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations of family functioning with body mass index in Mexican-origin adolescents living in the U.S.

Abstract: Mexican-origin adolescents have a high prevalence of obesity. Research is needed to understand how family context may shape adolescent BMI. This study examined longitudinal associations of family functioning variables with the Centers for Disease Control and Prevention’s modified BMI z-score (BMIaz) in 1,175 Mexican-origin adolescents, and explored interactions with acculturation. Adolescents (50% female, aged 11–13 y in 2005–06) were identified from an ongoing cohort study of Mexican-origin adults in Houston,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Receiving emotional support in the form of compliments was previously associated with increased physical activity in Latinas (Marquez, Norman, Fowler, Gans, & Marcus, 2018 ). Moreover, verbal encouragement by family has been identified as a facilitator of physical activity with parent-child dyads describing more support from each other than spousal dyads (Heredia et al, 2019 ). In our study, mothers viewed directives and daughters identified praise as forms of encouragement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Receiving emotional support in the form of compliments was previously associated with increased physical activity in Latinas (Marquez, Norman, Fowler, Gans, & Marcus, 2018 ). Moreover, verbal encouragement by family has been identified as a facilitator of physical activity with parent-child dyads describing more support from each other than spousal dyads (Heredia et al, 2019 ). In our study, mothers viewed directives and daughters identified praise as forms of encouragement.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, family functioning may serve an important focus of intervention for conditions such as obesity (Halliday et al, 2014 ). For example, high family functioning predicts greater decrease in body mass index in adolescent Mexican American girls (Heredia et al, 2019 ). The relationship between family functioning and obesity is likely bidirectional but longitudinal data suggests that poor family functioning in childhood is associated with obesity later in adolescence and early adulthood among females (Poulsen et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, sensitive parenting (involving support and low hostility) in early childhood predicted lower BMI during adolescence [50,56]. Finally, in a large, longitudinal study on family cohesion and conflict, Heredia and colleagues found that less family cohesion and more conflict predict steeper weight loss declines in Mexican-American girls from age 12 to 17 [59].…”
Section: Family Dynamics and Body Mass Index (Bmi)mentioning
confidence: 99%
“…In 2007, Barlow et al [7] proposed that comprehensive strategies incorporating family-based interventions, as well as changes in weight-related behaviors rather than weight loss goals, can lead to sustained improvements in medical and psychosocial outcomes for children and adolescents living with obesity. Numerous studies have delved into how family behaviors associated with lifestyle, such as diet, physical activity, feeding practices, parental roles, health care support, and parenting style, may influence the weight of adolescents [4,5,[8][9][10][11]. However, only a limited number of studies have explored the impact of broader family environmental factors, such as family functioning during mealtimes or the quality of the relationship between parents and adolescents, on the body composition and lifestyle of adolescents [6,12,13].…”
Section: Introductionmentioning
confidence: 99%